Statistical Analysis and Optimization of Ammonia Removal from Aqueous Solution by Zeolite and Ion-exchange Resin - Ding, Yuanhao (Université d'Ottawa / University of Ottawa, 2015)
The ability of natural zeolite and synthetic ion-exchange resin for ammonia removal from aqueous solution was studied through batch experiments. The results showed that both zeolite and ion-exchange resin were effective (up to 87% of removal) in eliminating ammonia from aqueous solution. Factorial design and response surface methodology were applied to evaluate and optimize the effects of pH, dose, contact time, temperature and initial ammonia concentration. Low pH condition was preferred with the optimum pH found to be 6 for both zeolite and ion-exchange resin. High dose generated high removal rate and low exchange capacity. Results of factorial design and response surface methodology showed that temperature was not a significant parameter. The model prediction was in good agreement with observed data (R2 = 0.969 for zeolite and R2 = 0.957 for resin, respectively). For zeolite, the optimum Qe was 22.90 mg/g achieved at pH=7 and initial ammonia concentration of 3000 mg/L. For ion-exchange resin, Qe of 28.78 mg/g was achieved at pH=6 and initial TAN concentration of 3000 mg/L. The reaction kinetics for both of them followed the Pseudo-second order kinetic model (R2=0.998 and R2=0.999, respectively). Equilibrium data were fitted to Langmuir and Freundlich isotherm models with Freundlich model providing a slightly better predication for zeolite (R2=0.992) and Langmuir providing more accurate prediction for ion-exchange resin (R2=0.996). The ion-exchange resin can be completely regenerated by 2N H2SO4.
Keywords: Ammonia; Zeolite; Ion-exchange resin; Isotherm; Factorial design; Response surface methodology